A novel library of -arylketones as potential inhibitors of α-glucosidase: Their design, synthesis, in vitro and in vivo studies. Issue 1 (December 2017) - Luthra, Tania; Agarwal, Rahul; Estari, Mamidala; Adepally, Uma; Sen, Subhabrata
Abstract α-glucosidase is an essential enzyme located at the brush border of intestines. It is an important therapeutic target for type II diabetes. Herein we have designed a library of novel α-arylketones as inhibitors of α-glucosidase (yeast origin)via scaffold hopping and bioisosteric modification of known inhibitors of α-glucosidase. The design was validated through molecular docking that revealed strong binding interactions of the newly designed compounds against α-glucosidase. A library comprising of 15 compounds was synthesized in a combinatorial fashion, where the advanced amide intermediates were accessed through "shot gun" synthesis. The final compounds were characterized by1 H, 13 C-NMR and with high resolution mass spectroscopy.In vitro screening of the compounds against yeast α-glucosidase revealed substantial inhibition with IC50 s in the range of 4–10 μM (the standard drug acarbose inhibits α-glucosidase with an IC50 of 9.95 μM). Reaction kinetics suggested mixed type inhibition. Finally, in vivo studies of the most active compound3c against Streptozotocin induced male albino Wistar rats revealed that its administration in the rats for about 4 weeks lead to a highly significant (P < 0.001) decrease in the fasting blood glucose (FBG) compared to the untreated diabetic rats. Moreover, lower dose of3c had better control over FBG in contrast to high-dose.